A slow-release fertilizer composite hydrogel and its preparation method and application
By using the slow-release fertilizer composite hydrogel prepared with raw materials such as lignocellulose nanofibers and clinopterite, the problems of low nitrogen, phosphorus and potassium release efficiency and insufficient structural stability in the prior art are solved, and the sustained release effect of urea and good water absorption and swelling performance are achieved.
Patent Information
- Application Number
- CN202410499944.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-04-24
AI Technical Summary
While improving nitrogen release efficiency and mechanical properties, existing sustained-release fertilizer hydrogels are difficult to achieve efficient release of nitrogen, phosphorus and potassium, and their structural stability and water retention capacity are insufficient.
Using raw materials such as lignocellulose nanofibers, clinopterite, acrylic acid and acrylamide, a composite hydrogel is prepared through the action of initiators and crosslinking agents. The -CONH2 group of urea is crosslinked with the hydrogel matrix to form a square embedded structure to enhance the density and stability of the hydrogel.
The prepared slow-release fertilizer composite hydrogel has obvious porous structure, smooth surface, small pore size and high porosity, achieving the sustained release effect of urea, and has good water absorption, swelling and water retention properties, and can withstand large water pressure and swelling cycles.
Smart Images

Figure CN118388288B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of slow-release fertilizers, and in particular relates to a slow-release fertilizer composite hydrogel and a preparation method and application thereof. Background Art
[0002] Nutrients and water play a vital role in plant growth and production, and fertilizers can directly supply the essential nutrients required for crop development. In agriculture and horticulture, fertilizers are widely used to improve harvest quality and yield. Nitrogen, as one of the most important elements in plant nutrition, is crucial to crop yield. Urea, which contains up to 46% nitrogen, is a commonly used nitrogen fertilizer. Existing studies have shown that urea, which has hydrophilicity and high water solubility of amide groups, still has defects in the efficient use of nitrogen by plants. After the application of urea, volatilization and leaching will occur, resulting in a large loss of nitrogen, which reduces the effective nitrogen absorption capacity of plants to only 20% to 30%, further leading to environmental problems such as eutrophication, soil acidification and global warming.
[0003] In recent years, slow-release fertilizers (SRFs) have been widely used in research and development because of their ability to improve nitrogen utilization efficiency and provide sustainable nitrogen supply for plant absorption; slow-release fertilizers can achieve a slower nitrogen release rate under the condition of nitrogen physical hindrance and chemical reaction, and also have the potential to absorb and retain water, which can reduce the number of fertilizations and improve the adverse conditions of low fertility and water shortage. As an alternative to slow-release fertilizer production, hydrogels are currently becoming a new product for agricultural planting and plant ecological restoration because of their high water absorption and excellent swelling properties.
[0004] Previous studies have shown that acrylic acid (AA) and acrylamide (AAM) are monomers with good biocompatibility and are easy to polymerize to form hydrogels. The hydrogels formed by them have the advantages of soft texture, high water absorption, good swelling ability and good flexibility, but their high friction and non-wear resistance will damage the surface integrity of the hydrogel, thereby affecting the overall stability of the hydrogel. It has become a trend to use natural micro / nano materials to improve the mechanical properties of hydrogels. For example, using lignocellulose nanofibers (LCNF) as hydrogel reinforcement materials can improve the mechanical properties, porosity and hydrophobicity of hydrogels, but the application of lignocellulose nanofibers in slow-release fertilizers is hindered by their inherent hydrophilicity; and using natural mineral zeolites as cross-linking agents to reinforce hydrogels will significantly change the structural properties of hydrogels, resulting in a significant decrease in the nitrogen release rate of slow-release fertilizer hydrogels, and the effective release of nitrogen cannot be achieved. How to obtain a slow-release fertilizer hydrogel that has high swelling, mechanical properties, water retention and stability, and can achieve efficient release of nitrogen, phosphorus and potassium is one of the unresolved issues. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a slow-release fertilizer composite hydrogel and a preparation method and application thereof.
[0006] The technical solution adopted to solve the technical problem is to provide a slow-release fertilizer composite hydrogel, which includes the following raw materials in parts by weight: 2 to 58 parts of lignocellulose nanofiber suspension, 0.05 to 0.15 parts of clinoptilolite, 5 to 15 parts of acrylic acid, 5 to 15 parts of acrylamide, 1 to 2 parts of initiator, 0.1 to 0.3 parts of cross-linking agent and 5 to 15 parts of urea.
[0007] The beneficial effects of the above technical scheme of the present invention are as follows: the slow-release fertilizer composite hydrogel prepared with the above raw materials presents an obvious porous structure, a smooth surface, a small pore size and a high porosity. The hydrogel matrix prepared with acrylic acid and acrylamide as raw materials under the action of an initiator and a cross-linking agent is soft in texture and has good swelling properties, and lignocellulose nanofibers, clinoptilolite and urea can be well embedded in the hydrogel matrix. After urea is doped into the hydrogel, the -CONH2 group in the urea can be well cross-linked to the hydrogel matrix and presents a square embedding form; the introduction of the lignocellulose nanofiber suspension can provide the hydrogel matrix with more carboxyl groups, amide side groups and a larger surface area to improve its cross-linking density. At the same time, the slow-release fertilizer composite hydrogel prepared by the present invention also has good swelling and re-swelling properties, and can withstand large water pressure and swelling cycles, because the affinity between the lignocellulose nanofiber suspension and the hydrogel matrix polymer chain is strong, and it can also trigger the additional chemical cross-linking effect of urea, so that the hydrogel network density is further improved. Compared with commercial urea (which dissolves rapidly within 60 minutes), the slow-release fertilizer composite hydrogel prepared by the present invention can achieve a slower release rate and a slow-release effect of up to 30 days. After adding lignocellulose nanofibers, the physical cross-linking effect in the hydrogel network increases, and urea is embedded in the hydrogel, and its slow-release behavior tends to be a relaxation mechanism. The slow-release fertilizer composite hydrogel prepared by the present invention has good water absorption, swelling and water retention effects, and can achieve a slow-release effect of urea.
[0008] Preferably, the slow-release fertilizer composite hydrogel comprises the following raw materials in parts by weight: 14 to 58 parts of lignocellulose nanofiber suspension, 0.1 part of clinoptilolite, 10 parts of acrylic acid, 10 parts of acrylamide, 1.6 parts of initiator, 0.1 part of cross-linking agent and 10 parts of urea.
[0009] More preferably, the lignocellulose nanofiber suspension is prepared by the following steps:
[0010] The unbleached fiber is mixed with water, ground in a high-speed rotor grinder to form a water suspension, then ground using an ultrafine friction grinder with a disc gap of less than 90 μm, and then homogenized twice by a microfluidic machine at a pressure of 200 to 220 MPa to obtain the product.
[0011] More preferably, the initiator is potassium persulfate, sodium persulfate or ammonium persulfate; and the cross-linking agent is N,N-methylenebisacrylamide.
[0012] More preferably, the concentration of the lignocellulose nanofiber suspension is 3-4%.
[0013] The present invention also provides a method for preparing the above-mentioned slow-release fertilizer composite hydrogel, comprising the following steps:
[0014] (1) dissolving urea, clinoptilolite, acrylamide, a crosslinking agent and an initiator in water respectively to obtain a urea solution, a clinoptilolite suspension, an acrylamide aqueous solution, a crosslinking agent aqueous solution and an initiator aqueous solution;
[0015] (2) mixing and stirring the lignocellulose nanofiber suspension, the urea solution and the clinoptilolite suspension to obtain a premixed solution;
[0016] (3) adjusting the pH of acrylic acid to 4-5 to obtain pretreated acrylic acid;
[0017] (4) adding pretreated acrylic acid, acrylamide aqueous solution, crosslinking agent aqueous solution and initiator aqueous solution to the premixed solution in sequence, reacting under heating and nitrogen blowing conditions to obtain a gel solution;
[0018] (5) The gel solution is washed with methanol and water in sequence, dried, and ground into powder to obtain the product.
[0019] Preferably, the mixing and stirring speed in step (2) is 100 to 150 rpm.
[0020] Preferably, in step (3), the pH of acrylic acid is adjusted to 5 to 7 mol·L -1 of sodium hydroxide solution for adjustment.
[0021] Preferably, step (4) comprises the following steps: adding pretreated acrylic acid, acrylamide aqueous solution, crosslinker aqueous solution and initiator aqueous solution to the premixed solution in sequence at time intervals of 10 to 15 minutes, stirring evenly at a speed of 150 to 200 rpm, heating to 65 to 75° C. and continuously introducing nitrogen, reacting for 1.5 to 2.5 hours to obtain a gel solution.
[0022] Preferably, in step (5), the drying temperature is 90-110° C. and the drying time is 1-2 days.
[0023] The present invention also provides application of the slow-release fertilizer composite hydrogel in agricultural planting.
[0024] The present invention has the following beneficial effects:
[0025] (1) The slow-release fertilizer composite hydrogel of the present invention has good overall stability, presents an obvious porous structure, and has small and uniform internal pores.
[0026] (2) The slow-release fertilizer composite hydrogel of the present invention has good water absorption, swelling and water retention effects, and has ideal controlled release performance and urea slow-release effect, and can be well used in agricultural crop and forestry plant planting and ecological restoration of difficult sites in urban and rural areas.
[0027] (3) The slow-release fertilizer composite hydrogel preparation method of the present invention is simple, the raw materials are easily available and the cost is low, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A model for controlling urea slow-release by composite hydrogel for slow-release fertilizer;
[0029] Figure 2 SEM micrographs of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1;
[0030] Figure 3 are FTIR images of the hydrogels, urea, lignocellulose nanofiber suspensions and clinoptilolite prepared in Examples 1 to 4 and Comparative Example 1;
[0031] Figure 4 are XRD patterns of the hydrogels, urea and lignocellulose nanofiber suspensions prepared in Examples 1 to 4 and Comparative Example 1;
[0032] Figure 5 is the TGA graph of the hydrogel and urea prepared in Examples 1 to 4 and Comparative Example 1;
[0033] Figure 6 It is the DTG graph of the hydrogel and urea prepared in Examples 1 to 4 and Comparative Example 1;
[0034] Figure 7 is a graph of gel mass fractions of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1;
[0035] Figure 8 is a graph of water absorption behavior of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1;
[0036] Fig. 9 It is a swelling cycle diagram of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1;
[0037] Fig.10 The hydrogels prepared in Examples 1 to 4 and Comparative Example 1 were -1 Deswelling behavior diagram in NaCl solution;
[0038] Fig.11The hydrogels prepared in Examples 1 to 4 and Comparative Example 1 were -1 Diagram of deswelling behavior in CaCl2 solution;
[0039] Fig.12 The hydrogels prepared in Examples 1 to 4 and Comparative Example 1 were -1 Deswelling behavior diagram in FeCl3 solution;
[0040] Fig.13 are first-order and second-order swelling kinetic curves of the hydrogels prepared in Example 4 and Comparative Example 1;
[0041] Fig.14 The water retention performance diagram of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1;
[0042] Fig.15 The cumulative urea release graph of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1;
[0043] Fig.16 The urea sustained-release behavior model curve diagram of the hydrogel prepared in Example 4 and Comparative Example 1;
[0044] Fig.17 The Fickian release fraction diagram of the urea release behavior of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1;
[0045] Fig.18 It is a relaxation mechanism ratio diagram of the urea release behavior of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION
[0046] The features and performance of the present invention are further described in detail below in conjunction with embodiments.
[0047] Example 1
[0048] A slow-release fertilizer composite hydrogel is characterized by comprising the following raw materials in parts by weight: 2.857 parts of a 3.5% lignocellulose nanofiber suspension, 0.1 part of clinoptilolite, 10 parts of acrylic acid, 10 parts of acrylamide, 1.6 parts of ammonium persulfate, 0.1 part of N,N-methylenebisacrylamide and 10 parts of urea.
[0049] The 3.5% lignocellulose nanofiber suspension was prepared by the following steps:
[0050] The unbleached fibers were mixed with water, ground in a high-speed rotor grinder to form a water suspension with a concentration of 3.5%, and then ground using an ultrafine friction grinder with a disc gap of less than 90 μm. The suspension was homogenized twice using a microfluidic machine at a pressure of 208 MPa to obtain the product.
[0051] The method for preparing the slow-release fertilizer composite hydrogel in this embodiment comprises the following steps:
[0052] (1) dissolving urea in 50 parts of deionized water to obtain a urea solution; dispersing clinoptilolite in 5 parts of deionized water by ultrasonication to obtain a clinoptilolite suspension; weighing acrylamide, N,N-methylenebisacrylamide and ammonium persulfate and dissolving them in 5 parts of deionized water respectively to obtain an acrylamide aqueous solution, an N,N-methylenebisacrylamide aqueous solution and an ammonium persulfate aqueous solution;
[0053] (2) mixing a 3.5% lignocellulose nanofiber suspension, a urea solution and a clinoptilolite suspension, transferring the mixture into a double-necked flask and stirring the mixture at 100 rpm for 15 min to obtain a premixed solution;
[0054] (3) Using a concentration of 6 mol·L -1 The pH value of acrylic acid is adjusted to 4.5 by using sodium hydroxide solution to obtain pretreated acrylic acid;
[0055] (4) adding pretreated acrylic acid, acrylamide aqueous solution, N,N-methylenebisacrylamide aqueous solution and ammonium persulfate aqueous solution to the premixed solution at intervals of 15 minutes, stirring at a speed of 200 rpm, heating to 70° C. and continuously introducing nitrogen to remove oxygen, reacting for 2 hours to obtain a gel solution;
[0056] (5) The gel solution is sequentially immersed in methanol and water for washing to remove the residue, and then placed in an oven at 100°C for drying for 1 day, and ground into powder to obtain the obtained product.
[0057] Example 2
[0058] A slow-release fertilizer composite hydrogel is characterized by comprising the following raw materials in parts by weight: 14.286 parts of a 3.5% lignocellulose nanofiber suspension, 0.1 part of clinoptilolite, 10 parts of acrylic acid, 10 parts of acrylamide, 1.6 parts of ammonium persulfate, 0.1 part of N,N-methylenebisacrylamide and 10 parts of urea.
[0059] The 3.5% lignocellulose nanofiber suspension was prepared by the following steps:
[0060] The unbleached fibers were mixed with water, ground in a high-speed rotor grinder to form a water suspension with a concentration of 3.5%, and then ground using an ultrafine friction grinder with a disc gap of less than 90 μm. The suspension was homogenized twice using a microfluidic machine at a pressure of 208 MPa to obtain the product.
[0061] The method for preparing the slow-release fertilizer composite hydrogel in this embodiment comprises the following steps:
[0062] (1) dissolving urea in 50 parts of deionized water to obtain a urea solution; dispersing clinoptilolite in 5 parts of deionized water by ultrasonication to obtain a clinoptilolite suspension; weighing acrylamide, N,N-methylenebisacrylamide and ammonium persulfate and dissolving them in 5 parts of deionized water respectively to obtain an acrylamide aqueous solution, an N,N-methylenebisacrylamide aqueous solution and an ammonium persulfate aqueous solution;
[0063] (2) mixing a 3.5% lignocellulose nanofiber suspension, a urea solution and a clinoptilolite suspension, transferring the mixture into a double-necked flask and stirring the mixture at 100 rpm for 15 min to obtain a premixed solution;
[0064] (3) Using a concentration of 6 mol·L -1 The pH value of acrylic acid is adjusted to 4.5 by using sodium hydroxide solution to obtain pretreated acrylic acid;
[0065] (4) adding pretreated acrylic acid, acrylamide aqueous solution, N,N-methylenebisacrylamide aqueous solution and ammonium persulfate aqueous solution to the premixed solution at intervals of 15 minutes, stirring at a speed of 200 rpm, heating to 70° C. and continuously introducing nitrogen to remove oxygen, reacting for 2 hours to obtain a gel solution;
[0066] (5) The gel solution is sequentially immersed in methanol and water for washing to remove the residue, and then placed in an oven at 100°C for drying for 1 day, and ground into powder to obtain the obtained product.
[0067] Example 3
[0068] A slow-release fertilizer composite hydrogel is characterized by comprising the following raw materials in parts by weight: 28.571 parts of a 3.5% lignocellulose nanofiber suspension, 0.1 part of clinoptilolite, 10 parts of acrylic acid, 10 parts of acrylamide, 1.6 parts of ammonium persulfate, 0.1 part of N,N-methylenebisacrylamide and 10 parts of urea.
[0069] The 3.5% lignocellulose nanofiber suspension was prepared by the following steps:
[0070] The unbleached fibers were mixed with water, ground in a high-speed rotor grinder to form a water suspension with a concentration of 3.5%, and then ground using an ultrafine friction grinder with a disc gap of less than 90 μm. The suspension was homogenized twice using a microfluidic machine at a pressure of 208 MPa to obtain the product.
[0071] The method for preparing the slow-release fertilizer composite hydrogel in this embodiment comprises the following steps:
[0072] (1) dissolving urea in 50 parts of deionized water to obtain a urea solution; dispersing clinoptilolite in 5 parts of deionized water by ultrasonication to obtain a clinoptilolite suspension; weighing acrylamide, N,N-methylenebisacrylamide and ammonium persulfate and dissolving them in 5 parts of deionized water respectively to obtain an acrylamide aqueous solution, an N,N-methylenebisacrylamide aqueous solution and an ammonium persulfate aqueous solution;
[0073] (2) mixing a 3.5% lignocellulose nanofiber suspension, a urea solution and a clinoptilolite suspension, transferring the mixture into a double-necked flask and stirring the mixture at 100 rpm for 15 min to obtain a premixed solution;
[0074] (3) Using a concentration of 6 mol·L -1 The pH value of acrylic acid is adjusted to 4.5 by using sodium hydroxide solution to obtain pretreated acrylic acid;
[0075] (4) adding pretreated acrylic acid, acrylamide aqueous solution, N,N-methylenebisacrylamide aqueous solution and ammonium persulfate aqueous solution to the premixed solution at intervals of 15 minutes, stirring at a speed of 200 rpm, heating to 70° C. and continuously introducing nitrogen to remove oxygen, reacting for 2 hours to obtain a gel solution;
[0076] (5) The gel solution is sequentially immersed in methanol and water for washing to remove the residue, and then placed in an oven at 100°C for drying for 1 day, and ground into powder to obtain the obtained product.
[0077] Example 4
[0078] A slow-release fertilizer composite hydrogel is characterized by comprising the following raw materials in parts by weight: 57.143 parts of a 3.5% lignocellulose nanofiber suspension, 0.1 part of clinoptilolite, 10 parts of acrylic acid, 10 parts of acrylamide, 1.6 parts of ammonium persulfate, 0.1 part of N,N-methylenebisacrylamide and 10 parts of urea.
[0079] The 3.5% lignocellulose nanofiber suspension was prepared by the following steps:
[0080] The unbleached fibers were mixed with water, ground in a high-speed rotor grinder to form a water suspension with a concentration of 3.5%, and then ground using an ultrafine friction grinder with a disc gap of less than 90 μm. The suspension was homogenized twice using a microfluidic machine at a pressure of 208 MPa to obtain the product.
[0081] The method for preparing the slow-release fertilizer composite hydrogel in this embodiment comprises the following steps:
[0082] (1) dissolving urea in 50 parts of deionized water to obtain a urea solution; dispersing clinoptilolite in 5 parts of deionized water by ultrasonication to obtain a clinoptilolite suspension; weighing acrylamide, N,N-methylenebisacrylamide and ammonium persulfate and dissolving them in 5 parts of deionized water respectively to obtain an acrylamide aqueous solution, an N,N-methylenebisacrylamide aqueous solution and an ammonium persulfate aqueous solution;
[0083] (2) mixing a 3.5% lignocellulose nanofiber suspension, a urea solution and a clinoptilolite suspension, transferring the mixture into a double-necked flask and stirring the mixture at 100 rpm for 15 min to obtain a premixed solution;
[0084] (3) Using a concentration of 6 mol·L -1 The pH value of acrylic acid is adjusted to 4.5 by using sodium hydroxide solution to obtain pretreated acrylic acid;
[0085] (4) adding pretreated acrylic acid, acrylamide aqueous solution, N,N-methylenebisacrylamide aqueous solution and ammonium persulfate aqueous solution to the premixed solution at intervals of 15 minutes, stirring at a speed of 200 rpm, heating to 70° C. and continuously introducing nitrogen to remove oxygen, reacting for 2 hours to obtain a gel solution;
[0086] (5) The gel solution is sequentially immersed in methanol and water for washing to remove the residue, and then placed in an oven at 100°C for drying for 1 day, and ground into powder to obtain the obtained product.
[0087] Comparative Example 1
[0088] A slow-release fertilizer composite hydrogel is characterized by comprising the following raw materials in parts by weight: 0.1 parts of clinoptilolite, 10 parts of acrylic acid, 10 parts of acrylamide, 1.6 parts of ammonium persulfate, 0.1 parts of N,N-methylenebisacrylamide and 10 parts of urea.
[0089] The method for preparing the slow-release fertilizer composite hydrogel in this embodiment comprises the following steps:
[0090] (1) dissolving urea in 50 parts of deionized water to obtain a urea solution; dispersing clinoptilolite in 5 parts of deionized water by ultrasonication to obtain a clinoptilolite suspension; weighing acrylamide, N,N-methylenebisacrylamide and ammonium persulfate and dissolving them in 5 parts of deionized water respectively to obtain an acrylamide aqueous solution, an N,N-methylenebisacrylamide aqueous solution and an ammonium persulfate aqueous solution;
[0091] (2) Mix the urea solution and the clinoptilolite suspension, transfer them into a two-necked flask and stir at 100 rpm for 15 min to obtain a premixed solution;
[0092] (3) Using a concentration of 6 mol·L -1The pH value of acrylic acid is adjusted to 4.5 by using sodium hydroxide solution to obtain pretreated acrylic acid;
[0093] (4) adding pretreated acrylic acid, acrylamide aqueous solution, N,N-methylenebisacrylamide aqueous solution and ammonium persulfate aqueous solution to the premixed solution at intervals of 15 minutes, stirring at a speed of 200 rpm, heating to 70° C. and continuously introducing nitrogen to remove oxygen, reacting for 2 hours to obtain a gel solution;
[0094] (5) The gel solution is sequentially immersed in methanol and water for washing to remove the residue, and then placed in an oven at 100°C for drying for 1 day, and ground into powder to obtain the obtained product.
[0095] Experimental example
[0096] 1. Characterization of slow-release fertilizer composite hydrogel
[0097] (1) Fourier transform infrared spectroscopy (FTIR, Tensor 27, Bruker Corp., Billerica, MA, USA) was used at 4000-500 cm -1 The range is 16cm -1 Pure urea, LCNF, clinoptilolite, slow-release fertilizer composite hydrogels prepared in Examples 1 to 4 and Comparative Example 1 were analyzed in attenuated total reflection (ATR) mode with a resolution of 1000 nm; the crystal structure of the slow-release fertilizer composite hydrogel was analyzed by X-ray diffraction (XRD), and the diffraction patterns were recorded in Bragg-Brentano geometry (θ-2θ) on a Bruker AXSD-8 diffractometer (Bruker Corp., Billerica, MA, USA) using Cu-Kα radiation (λ=0.154 nm), operated at 40 kV, with a scan rate of 2 min -1 ; Scanning electron microscopy (SEM) of the slow-release fertilizer composite hydrogel structure was performed using FEIQuanta 200-ESEM at an accelerating voltage of 20 kV; Thermogravimetric analysis (TGA) was performed using a thermogravimetric analyzer (Q500, TAInstruments, Newcastle, DE, USA) to analyze the thermal stability of the prepared slow-release fertilizer composite hydrogel. The results are shown in Figures 2 to 6 shown.
[0098] from Figure 2It can be seen that the slow-release fertilizer composite hydrogel has an obvious porous structure, while the hydrogel prepared in Comparative Example 1 without adding LCNF shows the rough morphology of nanofibers and urea. In Examples 1 to 4, as the LCNF content increases, the surface of the slow-release fertilizer composite hydrogel becomes smoother, with a smaller pore size and a higher porosity. At the same time, the morphological structure of urea disappears in the slow-release fertilizer composite hydrogels prepared in Examples 2 to 4, indicating that urea is better integrated into the hydrogel matrix; among them, the slow-release fertilizer composite hydrogel prepared in Example 4 shows an outstanding high porosity and uniform micropore distribution.
[0099] from Figure 3 As can be seen, the absorption peaks of urea spectrum are located at 3432, 3332 and 1587 cm -1 The asymmetric and symmetric stretching vibrations of NH in -CONH2 and NH deformation are 1673 and 1457 cm -1 The absorption peaks at 1703-1319 cm-1 are attributed to the stretching vibration of -CO and CN in -CONH2. -1 There is a strong absorption peak at 1703 cm -1 ) and the stretching vibration of the conjugated carbonyl groups of lignin (1647 cm -1 ), the stretching vibration of C=C in the aromatic skeleton of lignin (1520cm -1 ) and methyl (-CH3) asymmetric and symmetric bending vibrations (1457 and 1319 cm -1 ); In addition, COC, CO and C-OH in LCNF are at 1028cm -1 There is a broad peak near 1010cm -1 The strong Si-O(Si)(Al) absorption peaks at 1636, 793 and 596 cm -1 The other peaks at 3432 cm-1 and 3332 cm-1 correspond to HOH bending vibration, Si-O (Si) and SiO (Al) stretching vibration. -1 Moved to 3186cm -1 , at 1673, 1587 and 1457 cm -1 Compared with the absorption peaks of urea alone, the absorption peaks at - The NH and CN in -C=O, -NH2, and -CONH2 are bent and move to 1654, 1546, and 1446 cm-1, respectively. -1 ; This indicates that the (-CONH2) groups in urea are successfully cross-linked into the hydrogel matrix; at the same time, the clinoptilolite -1The peaks at 3343, 2937, and 1546–1100 cm -1 The absorption peaks at 1654, 1543 and 1394 cm correspond to the overlapping absorption bands of OH in acrylic acid, CH and CO of -CH2 in monomer, and CN and OH bending coupling. -1 The absorption peak at 40° increased and became sharper, which may be due to the incorporation of LCNF and urea, which led to the strengthening of C=O bond and C=C aromatic skeleton and the - And -CH3 groups increase.
[0100] from Figure 4 It can be seen that the hydrogel after adding urea has a broad peak between 2θ=15 and 27°, indicating that it is an amorphous structure. In the XRD spectrum of the hydrogel, characteristic diffraction peaks of urea at 2θ=22.5°, 24.9°, 29.5°, 35.7° and 37.3° were observed, and a strong peak (marked with "+") appeared at 2θ=22.4°~37.3°, indicating that urea was successfully embedded in the hydrogel matrix in a tetragonal form. The diffraction peaks are located near 2θ=22.1° and 31.9°, corresponding to the presence of clinoptilolite. In the hydrogel nanocomposites with a high LCNF content (Examples 2 to 4), the characteristic peaks and ideal relative crystallinity of clinoptilolite are 100%. In Example 1, the diffraction peak of clinoptilolite at 2θ=31.9° is weak. The typical diffraction peak is located at 2θ = 22.7°, corresponding to the (200) reflection domain of the cellulose structure, and in the hydrogels containing Example 1 and Example 4, the crystallinity is 100% and 94.15%, respectively, and a clear diffraction peak appears near 2θ = 22.7°. In addition, the diffraction pattern of Example 4 shows a clear diffraction peak and high crystallinity in the range of 2θ = 22.1° to 23.8°, which may be due to the enhanced diffraction caused by the incorporation of LCNF, clinoptilolite and urea. The increase in relative crystallinity indicates that there is a strong interaction between the hydroxyl radicals of the polymer and LCNF, however, the complexation between them may destroy the original structure of the copolymer, resulting in a decrease in crystallinity.
[0101] In addition, in this study, TGA and DTA analysis showed that ( Figures 5-6and Table 1), the hydrogels prepared in the present invention all exhibited four-step thermal decomposition behavior, including three different endothermic steps and one fluctuation period. The weight loss before 100°C is the result of water evaporation. The initial thermal degradation of the hydrogel occurred in the range of 165°C to 245°C, where the weight loss was mainly attributed to the thermal decomposition of the ester carbonyl group. The second step between 265°C and 306°C was attributed to the cleavage of the COC bond. Due to the thermal decomposition of the carboxyl and amide side groups and the structure of the cellulose nanofibril main chain, the third step occurred between 306°C and 370°C, which triggered the dehydration and chain decomposition of the hydrogel and released volatile compounds such as water vapor, CO2, NH3, and CH4. The last stage was above 385°C, and the fluctuation curve indicated many processes, including polymer main chain decomposition, CC bond cleavage, and residue carbonization. In addition, the weight became constant at around 485°C, indicating that the LCNF degradation was complete. The initial thermal degradation temperature (T0) of the hydrogel, the 20% weight loss temperature (T d20 ), maximum weight loss temperature (T max ) and the amount of residual carbon are shown in Table 1.
[0102] Table 1 T0, T2 of the hydrogels of Examples 1 to 4 and Comparative Example 1 d20 and T max value
[0103]
[0104]
[0105] Compared with Comparative Example 1, T0 increases with the increase of LCNF content, T d20 As the LCNF content increases (Examples 1-2). However, the hydrogel T of Example 4 d20 The highest T d20 is 248.77℃. As the LCNF content increases, T max The increase in T0 after adding LCNF may be due to the interaction between LCNF and the polymer matrix, which leads to an increase in the degradation temperature of the hydrogel; excessive LCNF may damage the hydrogen bonds and weaken the resistance of the polymer chain, while the introduction of LCNF will introduce more carboxyl and amide side groups and a larger surface into the hydrogel matrix, which will lead to the hydrogel of Example 4 having a lower T d20 and T max In addition, the hydrogel of Comparative Example 1 exhibits a more stable degradation rate and a higher residue ratio, which is due to the fact that the hydrogel containing a certain amount of urea releases ammonia to form more stable cyclic compounds.
[0106] (2) The slow-release fertilizer composite hydrogel was weighed and recorded as W0, then immersed in water, taken out after 48 hours and air-dried to constant weight and recorded as W1, and the gel mass fraction (GMF) of the slow-release fertilizer composite hydrogel was calculated as follows:
[0107]
[0108] Put the slow-release fertilizer composite hydrogel into the mesh bag and weigh it as W i , and then soak it in water at room temperature until swelling equilibrium; take out the swollen slow-release fertilizer composite hydrogel within time (t), suspend it in the air until no water droplets remain, and weigh it and record it as W t , calculate the swelling degree (S e ), and calculate as follows:
[0109]
[0110] The slow-release fertilizer composite hydrogel was encapsulated in a nylon bag and weighed as W0. It was immersed in distilled water until swelling equilibrium was reached and then taken out and weighed as W. eq ; Then, the swollen slow-release fertilizer composite hydrogel was dried at 80°C, and the weight of the slow-release fertilizer composite hydrogel at different time intervals during the drying process was recorded as W t , calculate the water retention rate (WR) of the slow-release fertilizer composite hydrogel, where when t = 0, W t =W0; calculate according to the following formula:
[0111]
[0112] The results are as follows Figures 7 to 9 As shown, except for Example 2, the GMF of the hydrogels containing LCNF increased with the increase of LCNF content (the lowest GMF was 51.80%). In contrast, the GMF of the hydrogel of Example 4 reached 82.20%. The increase in GMF is attributed to the affinity between LCNF and polymer chains, which acts as an enhancer. The GMF value of the hydrogel of Example 1 is higher than that of the hydrogel of Comparative Example 1 (up to 90.4%), which may be caused by the additional chemical cross-linking effect of urea. At the same time, the water absorption of all hydrogels reached equilibrium on the 7th day, and the maximum water absorption of the hydrogel of Example 1 was 94.29 (g·g -1 ). At the same time, the water absorption rate of the hydrogel samples decreased with the increase of LCNF content. The water absorption rate of the hydrogel of Example 4 was the lowest, 24.04 (g·g -1), which may be due to the enhanced interfacial bonding established between the hydrogel matrix and the fibers with the increase in LCNF content. During 5 swelling cycles, the loss of the reswelling ability of the hydrogel decreased with the increase in LCNF; after 5 reswelling cycles, the hydrogel of Example 4 exhibited a minimum swelling ability loss of 23.52%, which decreased from 27.231 (g·g -1 ) to 20.827 (g·g -1 ) compared to the first cycle. The swelling degree losses of the hydrogels of Examples 1-3 and Comparative Example 1 were 32.91%, 32.60%, 25.65%, and 28.63%, respectively; this decrease in swelling ability can be attributed to the vulnerability of the hydrogel to water pressure, resulting in partial breakage of the polymer chains and collapse of the voids within the hydrogel structure. However, with the increase in LCNF content, the reswelling ability improved, which was due to the enhanced crosslinking effect introduced by LCNF that increased the denseness of the hydrogel network. Therefore, the hydrogel of Example 4 exhibited better reswelling performance and could withstand more water pressure and swelling cycles.
[0113] 2. Water Absorption and Swelling Kinetics of the Sustained-Release Fertilizer Composite Hydrogel
[0114] The swelling is caused by the diffusion of water in the polymer matrix, which is characterized by the movement of polymer segments, resulting in a significant separation of the macromolecular chains over long distances. By analyzing the initial 60% fractional liquid absorption, the following water diffusion mechanism was determined:
[0115]
[0116] where, W t and W ∞ represent the water absorption capacity at time t and at equilibrium, respectively. The constant k represents the inherent property of the hydrogel sample, while the exponent n characterizes the diffusion mechanism of water molecules. When n < 0.5, the diffusion follows the Fickian diffusion model. In the range of 0.5 < n < 1.0, the diffusion is controlled by the non-Fickian or anomalous diffusion model, where both polymer chain relaxation and water diffusion affect water absorption. A value of n = 1 represents Case-II diffusion, where polymer chain relaxation controls water diffusion, and n > 1 represents super Case-II diffusion. The diffusion coefficient for the first 60% of the equilibrium capacity was determined using the short-time approximation method:
[0117]
[0118] where, D is the diffusion coefficient (cm 2 min -1 ) at the soaking time t (min), and r is the thickness (cm) of the hydrogel sample. By comparing equations (4)-(6) and assuming n = 1 / 2, the following relationship can be obtained:
[0119] k 1 / 2 =4(D / πr 2 ) 1 / 2 (6)
[0120]
[0121] The water absorption rate was investigated using the first-order kinetic model:
[0122]
[0123] The water absorption rate constant is k at the absorption time t (min). w (min -1 ).
[0124] The swelling / swelling behavior of the hydrogel nanocomposites was evaluated to demonstrate their performance in adverse environments. Swelling tests were conducted in saline environments; the dried samples were immersed in 0.1 mol·L -1 The dried sample is first weighed and then the swelling is measured. The swollen sample is then dried to a constant weight. This process is repeated 6 times and the equilibrium water loss is calculated using formula (2).
[0125] The swelling kinetics were investigated by fitting first-order and second-order models. In the former, the swelling rate was independent of time and was related to reaching the maximum or equilibrium uptake (W ∞ ) before swelling capacity (W ∞ -W t ), which can be expressed as:
[0126]
[0127] Where W t represents the solvent absorption or swelling at time (t), and K is the proportional constant between the swelling rate and the swelling capacity. Transform equation (10) into:
[0128]
[0129] There is a linear relationship between ln(W ∞ / W ∞ -W t The second stage adopts Schott pseudo-second-order expansion kinetic model:
[0130] t / W=A+Bt (11)
[0131]
[0132] B=1 / W∞ (13)
[0133] In the formula, A(g min g -1 ) is the initial expansion rate [(d W / d t )0]. By comparing equations (11) to (13), equation (14) can be organized as:
[0134]
[0135] In the formula, Wt(g·g -1 ) is the expansion capacity at any time t(s); W ∞ (g·g -1 ) represents the theoretical equilibrium expansion; Ks(g·g -1 min -1 ) is the initial expansion rate constant. W ∞ and K s Respectively represents t / W t The slope and intercept of the curve relative to t.
[0136] The swollen hydrogel sample was at 0.1 mol·L -1 The swelling behavior results in NaCl, FeCl3 and CaCl2 solutions are as follows Figures 10-12 As shown. Figures 10-12 It can be seen that the swelling ability of the hydrogel sample in the saline solution decreases rapidly in the first 15 minutes, the swelling degree is low in the NaCl solution, and the swelling degree is high in the CaCl2 and FeCl3 solutions. In the NaCl solution, the swelling amount of Example 1 is reduced by 62.95% at the maximum and 35.07% at the minimum. In the CaCl2 and FeCl3 solutions, the swelling ability of all hydrogels decreased by more than 80%; among them, the swelling rates of the hydrogels in Example 1 were 95.78% and 94.69%, respectively, and those in Example 4 were 83.64% and 87.79%, respectively. The hydrogels showed a higher degree of swelling in CaCl2 and FeCl3 solutions, which may be due to the establishment of stronger ionic crosslinking points in the hydrogels with higher cationic charges. At the same time, the addition of LCNF helps to strengthen the crosslinked three-dimensional network and delay the shrinkage of the hydrogel.
[0137] The swelling kinetics and related parameters of the hydrogels of Example 4 and Comparative Example 1 were studied. Fig.13 As shown in Table 2.
[0138] Table 2 Swelling and water absorption dynamic parameters of hydrogels in Example 4 and Comparative Example 1
[0139]
[0140] from Fig.13and the curves and R in Table 2 2 It can be seen from the values that the swelling of the two samples is more in line with the second-order kinetics, indicating that the water absorption rate is related to the surface properties. In addition, compared with the hydrogel of Comparative Example 1 (7.782 g min -1 g -1 ), the hydrogel of Example 4 exhibited a lower K S Value (4.518 g min -1 g -1 ), indicating that the swelling of the hydrogel is slow after the incorporation of LCNF. For the hydrogels of Comparative Example 1 and Example 4, the n values are 0.232 and 0.331, respectively, both less than 0.5, which indicates that the water absorption behavior of the hydrogel follows the Fickian mechanism and the water diffusion in the hydrogel network is controlled by water diffusion.
[0141] In addition, the kinetic parameters of the water diffusion mechanism of the hydrogels of Examples 1 to 4 and Comparative Example 1 were studied, as shown in Table 3.
[0142] Table 3 Water diffusion parameters of hydrogels in Examples 1 to 4 and Comparative Example 1
[0143]
[0144] As can be seen from Table 3, the hydrogel prepared in Example 4 showed a minimum D of 0.0056 cm 2 min -1 , K w 0.00083min -1 , indicating that the diffusion rate of water transported into the hydrogel network is slow. In addition, with the increase of LCNF content (Examples 2-4), the values of D and Kw decreased, indicating that the incorporation of LCNF limits the diffusion of water, which is attributed to the enhancement of the compact and highly cross-linked three-dimensional structure, which in turn limits the flow of water into the hydrogel network.
[0145] In addition, the water retention properties of the hydrogels of Examples 1 to 4 and Comparative Example 1 at a constant temperature (80°C) were studied. Fig.14 As shown. Fig.14 It can be seen that the hydrogel can maintain a constant amount of water for up to 45 hours. The hydrogel of Example 4 showed the best water retention capacity, with a slow water loss rate, and finally maintained a maximum water holding capacity of 39.20%, while the hydrogel of Example 3 had a faster water loss rate before reaching a constant value, but the water holding capacity was maintained at a higher percentage of 32.30%. The final water retention capacity increased with the increase in the amount of LCNF added, indicating that nanofiber crystallization can promote the diffusion of water. At the same time, urea, as a cross-linking agent, forms a three-dimensional network in the hydrogel, which can improve water absorption and water holding capacity.
[0146] 3. Release of urea in slow-release fertilizer composite hydrogel in water and release kinetics analysis
[0147] Weigh 1g of urea, hydrogels prepared in Examples 1 to 4 and Comparative Example 1, respectively, and place them in a nylon mesh bag and immerse them in 500mL of deionized water. Sampling and measurement are performed every 5min, 10min, 30min, 1h, 2h, 5h, 1d, 3d, 8d, 15d and 25d. Each time, 1mL of solution is sampled and 1mL of deionized water is added to keep the total volume constant. In a dark room, 3mL of deionized water, 1mL of sulfuric acid (2mol·L -1 ) and 5 mL PDAB were added to a Falcon centrifuge tube in sequence. After 10 min of color development, the extract solution was measured using a UV spectrum at 422 nm. The following model was used to further study the urea release kinetics:
[0148] Korsmeyer-Peppas Model:
[0149] Higuchi Model:
[0150] Peppas-Sahlin Model:
[0151] Zero-order kinetic model:
[0152] First-order kinetics:
[0153] Where M t / M ∞ is the fertilizer release fraction in the equilibrium state at time t; t is the release time, K KP and n are the release constant and diffusion exponent, respectively; k1 and k2 are the diffusion constants associated with Fickian and non-Fickian mechanisms, and m is the pure Fickian diffusion exponent coefficient for controlled release devices of any geometry; K His the Higuchi dissolution constant; K0 and K1 are the release constants of the zero-order and first-order models, respectively. The Korsmeyer-Peppas model describes the release pattern of fertilizers, including Fickian and non-Fickian behaviors in swelling and release systems. The release mechanism of the slow-release fertilizer can be inferred based on the diffusion exponent n. If n < 0.45, the diffusion follows Fickian diffusion. In the range of 0.45 < n < 0.89, the diffusion follows a non-Fickian transport process. When n > 0.89, it is the most basic dissolution process. The Peppas-Sahlin model combines the Fickian diffusion contribution and non-Fickian diffusion contribution in a linear manner. It should be noted that these mathematical models are only applicable to the first 60% of urea release. The zero-order model describes the urea release behavior, which is concentration-independent and occurs at a constant rate within a defined time. In contrast, the first-order model is used to explain the release behavior, where the release rate remains constant within a specified time interval and is affected by the fertilizer concentration.
[0154] The results of cumulative urea release are shown as Fig.15 follows. The hydrogels prepared in Examples 1 to 4 showed a slower release rate and a release time of up to 30 d, while commercial urea dissolved completely rapidly within 60 min. The equilibrium amount of cumulative urea release varied with the content of LCNF (>0%) in the hydrogel. The hydrogel of Example 4 had a higher urea release equilibrium value of 52.75 mg·L -1 , and a slower release rate. The urea cumulative release rates of the hydrogels in Examples 1 to 4 were 29.09%, 32.16%, 25.86%, 16.37%, and 9.37% at 1 h, respectively. The slowdown of urea release can be attributed to the increase in physical cross-linking within the hydrogel network after adding LCNF. In addition, the content of LCNF may affect the entrapment of urea in the hydrogel matrix. The equilibrium release amount of urea in the hydrogel of Example 1 was relatively low, which may be due to the low encapsulation rate of urea in the hydrogel matrix.
[0155] The results of urea release kinetics and different model parameters are shown in Fig.16 and Table 4. The results showed that the urea release behaviors of the hydrogels in Example 4 and Comparative Example 1 were more in line with the Peppas-Sahlin model. Compared with Comparative Example 1, the k1 value of Example 4 was lower, at 0.577, and the k2 value was higher, at -0.154, indicating that its urea release behavior tended to the relaxation mechanism.
[0156] Table 4 Urea release kinetic parameters of the hydrogels in Example 4 and Comparative Example 1
[0157]
[0158] The percentage of urea release according to the Fickian mechanism (F) and the relaxation mechanism (R) is calculated as:
[0159]
[0160]
[0161] The calculated results are shown in Table 5 and Figures 17-18 shown.
[0162] Table 5 Peppas-Sahlin model parameters of the hydrogels of Examples 1 to 4 and Comparative Example 1
[0163]
[0164]
[0165] From Table 5 and Figures 17-18 It can be seen that the urea release behavior is dominated by the Fickian mechanism, and the advantage ratio increases with the extension of the release time. Both the relaxation constant k2 and the relaxation ratio are negative, indicating that the swelling behavior is limited during the urea release process. These results show that the release of urea from the slow-release fertilizer composite hydrogel is mainly controlled by urea diffusion, and the release fraction of the Fickian mechanism decreases with the increase of LCNF addition (Examples 1 to 3). The slow-release fertilizer composite hydrogel prepared in Example 3 has the smallest Fickian release fraction within 3d, which is 1.187, while the Fickian release fraction of the slow-release fertilizer composite hydrogel prepared in Example 4 increases to 1.821. However, the urea release behavior of the slow-release fertilizer composite hydrogel prepared in Example 4 can be carried out with an appropriate Fickian release fraction, which also explains Fig.16 The slower urea release rate was observed in
[0166] In summary, in the presence of lignocellulose nanofiber suspension / clinoptilolite / urea, N,N-methylenebisacrylamide was used as a cross-linking agent and an initiator was added. The slow-release fertilizer composite hydrogel was successfully prepared by free radical polymerization of acrylic acid and acrylamide, and the effect of the content of the lignocellulose nanofiber suspension on its structure, morphology and physical properties was studied. The results show that the slow-release fertilizer composite hydrogel prepared in Examples 1 to 4 has a lower water absorption rate than the hydrogel prepared in Comparative Example 1, a lower swelling loss, and an improved water retention capacity. In addition, the slow-release fertilizer composite hydrogel prepared by the present invention has a slower release rate and a release time of up to 30 days. The slow-release fertilizer composite hydrogel prepared in Example 4 slows down the release of urea by 14 days. The results show that the slow-release fertilizer composite hydrogel prepared by the present invention has good water absorption, swelling and water retention properties.
[0167] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.
Claims
1. A slow-release fertilizer composite hydrogel, characterized in that: The method is composed of the following raw materials in parts by weight: 2-58 parts of lignocellulose nanofiber suspension, 0.05-0.15 parts of clinoptilolite, 5-15 parts of acrylic acid, 5-15 parts of acrylamide, 1-2 parts of initiator, 0.1-0.3 parts of crosslinking agent and 5-15 parts of urea; The lignocellulose nanofiber suspension is prepared by the following steps: The unbleached fibers were mixed with water, ground in a high-speed rotor grinder to form an aqueous suspension, then ground using an ultrafine friction grinder with a disc gap of less than 90 µm, and then homogenized twice using a microfluidic machine at a pressure of 200-220 MPa to obtain; The concentration of the lignocellulose nanofiber suspension is 3-4%.
2. The slow-release fertilizer composite hydrogel according to claim 1, characterized in that: The invention is composed of the following raw materials in parts by weight: 14 to 58 parts of lignocellulose nanofiber suspension, 0.1 part of clinoptilolite, 10 parts of acrylic acid, 10 parts of acrylamide, 1.6 parts of initiator, 0.1 part of crosslinking agent and 10 parts of urea.
3. The slow-release fertilizer composite hydrogel according to claim 1 or 2, characterized in that: The initiator is potassium persulfate, sodium persulfate or ammonium persulfate; the cross-linking agent is N,N-methylenebisacrylamide.
4. The method for preparing the slow-release fertilizer composite hydrogel according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving urea, clinoptilolite, acrylamide, a crosslinking agent and an initiator in water respectively to obtain a urea solution, a clinoptilolite suspension, an acrylamide aqueous solution, a crosslinking agent aqueous solution and an initiator aqueous solution; (2) mixing and stirring the lignocellulose nanofiber suspension, the urea solution and the clinoptilolite suspension to obtain a premixed solution; (3) adjusting the pH of acrylic acid to 4-5 to obtain pretreated acrylic acid; (4) adding pretreated acrylic acid, acrylamide aqueous solution, crosslinking agent aqueous solution and initiator aqueous solution to the premixed solution in sequence, reacting under heating and nitrogen blowing conditions to obtain a gel solution; (5) The gel solution is washed with methanol and water in sequence, dried, and ground into powder to obtain the product.
5. The method for preparing the slow-release fertilizer composite hydrogel according to claim 4, characterized in that: The rotation speed of the mixing and stirring in step (2) is 100-150 rpm.
6. The method for preparing the slow-release fertilizer composite hydrogel according to claim 4, characterized in that: In the step (3), the pH of acrylic acid is adjusted to 5-7 mol·L −1 of sodium hydroxide solution for adjustment.
7. The method for preparing the slow-release fertilizer composite hydrogel according to claim 4, characterized in that: The step (4) comprises the following steps: adding pretreated acrylic acid, acrylamide aqueous solution, crosslinker aqueous solution and initiator aqueous solution to the premixed solution in sequence at time intervals of 10 to 15 minutes, stirring evenly at a speed of 150 to 200 rpm, heating to 65 to 75° C. and continuously introducing nitrogen, reacting for 1.5 to 2.5 hours to obtain a gel solution.
8. The method for preparing the slow-release fertilizer composite hydrogel according to claim 4, characterized in that: In the step (5), the drying temperature is 90-110° C. and the drying time is 1-2 days.
9. Use of the slow-release fertilizer composite hydrogel according to any one of claims 1 to 3 in agricultural planting.
Citation Information
Patent Citations
Lignocellulose nano-fiber / acrylic resin composite film preparation method
CN103396572A
Preparation method for multifunctional composite hydrogel slow-release fertilizer
CN107162747A
Zeolite-cellulose polyacrylamide composite hydrogel as well as preparation and application thereof
CN115678043A
Cited By
Functional slow-release fertilizer and preparation method thereof
CN121159336A